THE DESIGN AND DEVELOPMENT OF VOLTAGE AMPLIFIERS USING MICROCONTROLLER FOR MASS ABSOLUTE PRESSURE (MAP) SENSOR IN THE TOYOTA AVANZA - Wawan Purwanto; Agus Bahrudi1; Toto Sugiarto; Dwi Sudarno Putra; Nuzul Hidayat (Universitas Sultan Ageng Tirtayasa, 2018)
This research focus on the design of output voltage amplifier from MAP sensor. The purpose of this design research is to explain the process of designing and manufacturing and testing the voltage amplifier with Arduino Uno microcontroller and as a refinement of the previous tool which has been found but still using manual control. In addition, this research serves as a solution to the problems that researchers found in the field of vehicle performance began to decrease with the increasing age of vehicle usage. This type of research is level 3 research, researchers research and test to develop existing products. The object of this research is Toyota Avanza 1.3 G vehicle in 2010. Based on the research, it can be concluded that after adding the output voltage from the MAP sensor with variation of voltage addition of 0.3V, 0.5 V, and 0.7V, it can be concluded that there is an increase in power and torque significantly generated by the vehicle. The highest increase in power and torque occurs in the addition of MAP sensor output voltage of 0.5 V with a percentage increase of 85.87% and 28.4% when compared to power and torque without using a voltage amplifier on the MAP sensor output.